A new species of Odontothrips (Thysanoptera, Thripidae) from Fars province, Iran - Hakimara, Mahsa; Minaei, Kambiz (Zootaxa, 2019)
Mound and Palmer (1981) included the following eight genera in Megalurothrips genus-group: Ceratothrips, Ceratothripoides, Craspedothrips, Lefroyothrips, Megalurothrips, Odontothripiella, Odontothrips, and Projectothrips. However, a series of shared morphological characters, as well as their shared host-plant association with members of the plant family Fabaceae, indicates that Megalurothrips, Odontothrips, and Odontothripiella are particularly closely related (Xie et al. 2010). The species of these three genera all have a pair of dorso-apical setae on the first antennal segment, a character state that distinguishes them from most Thripinae (Zhang et al. 2018). Of these, Odontothrips is the most species-rich genus with 34 species distributed in the Palaearctic (ThripsWiki 2019). In Iran only 5 species (O. confusus, O. iranensis, O. loti, O. meliloti, O. phlomidinus) have been recorded (Minaei 2017). Despite more than 60 years since O. phlomidinus was described from Iran, this species remains known only from the type series (Priesner 1954). In this paper, a new species of the genus is described from southern Iran that seems to be close to O. phlomidinus. Moreover, a provisional key is provided, based on females, for six species recorded from Iran. Authority names are available on the web (ThripsWiki 2019).